Towards a sense of urgency for innovation realization: A case study on complacency asymmetries in interorganizational relations - Christina Marie Mitcheltree (Journal of Innovation and Entrepreneurship, 2023)
This paper seeks to explore the concept of complacency as a barrier to the sense of urgency within product innovation, by investigating the concept on behalf of interfirm project partners. More specifically, the study aims to understand complacency within the context of an industrial research project in Norway subject to material substitution of an energy transmission tower. As such, the study seeks to give a contextual understanding of complacency for innovation realization (e.g., innovation speed) from a single case study. The study identified different complacency mechanism asymmetries on behalf of the actors, as well as the varying reasons (drivers) to why urgency gaps may occur among actors. The urgency gaps were found to impact a sense of urgency and thus innovation speed negatively. The asymmetries are presented from the drivers: role understanding, competence, project intent, risk and trust. Moreover, the urgency gaps' implications for interorganizational project collaboration, and how they contribute to theory on industrial product innovation, are explained. The findings contribute with new insights on important mechanisms for how a sense of urgency may be enhanced in research projects subject to interorganizational innovation. Theoretical contributions thus relate to enhanced understanding of complacency asymmetry in product innovation collaboration, and how trust is an important dimension for urgency creation.
Keywords: 650; Case study; Aluminum; Complacency asymmetries; Innovation speed; Product innovation; Urgency